Developing a spreadsheet application for BQ production. - Adul Hamid, Razali; Chong, Wan Siang (Faculty of Built Environment, UTM, 2004)
The demand for information technology is continuously increasing. In the Quantity Surveying field, specific software for BQ production and estimating is widely available. However, there are still a lot of companies using the Microsoft Excel for doing calculation, scheduling and most imporlantly production of Bills of Quantities. However, these spreadsheet solutions does not offer total automation compared to the specific software as the BQ cannot be produced automatically. However, using the Visual Basic for Application (VBA) features in Microsoft Excel, this problem has been resolved. This paper presents the development of METa (Microsoft Excel For Taking-Off) which match the BQ production capabilities of the specific software. Each step in the development process was explained and the system architecture of this application is being highlighted. As a conclusion, a highly capable and user-friendly application for BQ production was developed using Microsoft Excel.